Importance of Soil Health and Water Management in Agriculture - Amit Biswas (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2026)
Sustainable agriculture and food production are based on the fertility and health of the soil. Maintaining and improving soil quality is essential as the world’s population continues to rise, putting more pressure on agricultural fields. In order to optimize yields, industrialized agriculture has mostly relied on synthetic fertilizers and pesticides. However, these methods have a negative impact on the environment and human health, which is leading many farmers to switch to organic methods that focus on long-term soil vitality. In addition to sequestering carbon, improving nutrient and water efficiency, decreasing erosion and runoff, and fostering biodiversity both above and below the soil surface, organic amendments and regenerative approaches hold great potential for creating healthy, rich soils. The growing worldwide water scarcity situation, which has a significant impact on agriculture, particularly in nations like India, highlights the need for water conservation in agriculture. Due to declining water supplies, which are made worse by climate change, agriculture, the world’s biggest user of water, confronts serious difficulties. Hence, this study discussed the importance of soil health and water management in agriculture.